Diagnostic and therapeutic dilemma in orofacial pain: A rare case of bilateral Eagle syndrome - Umesh Pradhan; Tika Ram Adhikari (SAGE Open Medical Case Reports, 2022)
Eagle’s syndrome is a collection of symptoms due to abnormal and/or elongated styloid process. This can irritate the various neurovascular structures that lie in its close proximity, mainly the glossopharyngeal nerve, leading to odynophagia, dysphagia, foreign body sensation, cervicofacial pain, and headache. It is a diagnosis of exclusion and needs high degree of clinical suspicion. It is a rare condition with no reported incidence in the Bhutanese population so far. In this article, we present a case of elongated styloid process that was causing persistent and troublesome orofacial pain in a patient, which was not relieved by medication. The patient underwent trans-oral styloidectomy, which helped cure his symptoms.